Serum hepcidin levels in multiple sclerosis. Issue 4 (October 2019) - Bsteh, Gabriel; Haschka, David; Tymoszuk, Piotr; Berek, Klaus; Petzer, Verena; Hegen, Harald; Wurth, Sebastian; Auer, Michael; Zinganell, Anne; Pauli, Franziska Di; Deisenhammer, Florian; Weiss, Guenter; et al.
Background: Brain iron accumulation is associated with multiple sclerosis (MS). Hepcidin is the master regulator of iron homeostasis and distribution. Dysregulation of hepcidin is a feature of different chronic inflammatory diseases but has not been investigated in MS so far. Objective: The aim of this study was to determine serum hepcidin levels of MS patients and healthy volunteers serving as controls and to investigate possible relations between hepcidin levels, disease activity and disease course. Methods: In a cross-sectional design, we measured serum hepcidin levels in 71 MS patients and 16 healthy controls (HC). MS patients were sub-grouped in active relapsing–remitting MS (aRRMS), inactive (i)RRMS, active progressive MS (aPMS) and inactive (i)PMS. Blood parameters were measured by standard laboratory methods. Results: Median hepcidin levels were 26.9 ng/ml (confidence interval (CI) 22.8; 30.9) in MS and 17.3 ng/ml (CI 12.8; 23.4) in HC with significant age and sex effects. Hepcidin correlates were in line with hepcidin as an indicator of iron stores. After correction for age and sex, hepcidin was neither associated with MS subgroups nor degree of disability and occurrence of relapses. Conclusions: Serum hepcidin levels are not associated with disease activity and disease course in MS.